CONTROL OF TUBERCULOSIS IN A BORDER CITY: ANALYSIS OF THE INSTITUTIONAL CAPACITY OF HEALTH SERVICES - Regiane Bezerra Campos; Reinaldo Antonio Silva-Sobrinho; Maria Eugênia Firmino Brunello; Adriana Zilly; Pedro Fredemir Palha; Tereza Cristina Scatena Villa (Universidade Federal do Paraná, 2018)
Objective: to analyze primary health care services regarding the control of tuberculosis in the city of Foz do Iguaçu, Paraná. Method: a cross-sectional study, of survey type, with quantitative approach aimed to assess the institutional capacity of the following dimensions of health care services to control TB: organization of the treatment of tuberculosis, coordination with the community, support to self-care, support to decision and design of the service delivery system, involving 105 health professionals from 14 units from December 2013 to January 2014, and in 2015 with the use of descriptive statistics and Anova analysis. Results: The worst capacity was that of the dimension coordination with the community, classified as low, with a mean of 3.2 and a standard deviation of 1.8. The highest rated dimension was support to self-care, classified as regular, with a mean of 6.9 and a standard deviation of 2.1. Conclusion: need for training of health professionals and compliance with the principles and guidelines of TB control programs and policies in primary health care were identified.